A Study Of The Predictive Effect Of Pre-Service Teacher Personal Knowledge Management Competency On Their Instructional Design Skills - Cheng, Eric (Journal of Knowledge Management Practice, 2011)
This paper aims to examine the relationship between the personal knowledge management (PKM) competency of pre-service teachers and their instructional design skills. Supporting the sustainable development of teachers as professionals in the knowledge society is a critical issue in teacher education. This study attempts to identify an empirical model and a curriculum framework for nurturing pre-service teachers’ PKM competency. Dorsey (2000) PKM skills were adopted for constructing the theoretical framework and the survey instrument. A quasi-experimental research design was used to collect data from pre-service teachers from Hong Kong’s largest teacher education institution. A structural equation model was applied to explore the predictive power of PKM competency on their instructional design. Results show that a four-factor PKM competency model, which consists of retrieving, analyzing, organizing and collaborative skills, was identified as a predictor of instructional design. Use of PKM tools, e-learning activities and collaborative action research for developing pre-service teacher PKM competency are recommended to teaching education institute.
Keywords: knowledge management; Personal knowledge management; Pre-service teacher; Teacher education